Gayatri in the Modern Era: Ritual Innovation and Universalization of a Mantra - Dalal, Neil (Religions of South Asia, 2023)
The Gayatri is a ubiquitous Vedic verbal ritual formula (mantra) in Brahmanical traditions and the modern period of Hinduism. This essay traces the Gayatri’s changing theological backgrounds, ritual contexts and political uses in the modern period. It seeks to understand the history of the Gayatri’s transformations in modern India, and questions how the Gayatri transitioned from a private initiation ritual in Vedic Brahmanical culture to a popular public mantra. Hindu reform movements at the turn of the twentieth century provide important clues for how the mantra may have become more public, particularly through reconversion rituals (suddhis) to Hinduism regardless of gender, religion, or caste. Reconversion rituals contributed to removing the Gayatri from the jurisdiction of orthodox Brahmanical authorities, and transformed it from a central symbol of twice-born Vedic identity into a broader symbol of Hindu identity. In some cases, the Gayatri is now universalized as a secular mantra in India, though one that maintains tacit Hindu or Indian nationalist identities.